Estudo de geração fotovoltaica em uma tornearia - Meira, Guilherme Campanerutti (2021)
Photovoltaic solar generation uses the incidence of solar rays that reach the planet Earth and is a form of inexhaustible and renewable generation. The present work has as focus to study the dimensioning of a photovoltaic mini-generation system connected to the concessionaire network, to be implemented in a turnery in the Northwest of Paraná. With the dimensioning of the photovoltaic power through consumption, using global horizontal irradiation data for the proper calculation of the dimensioning of the photovoltaic system. This study foresees that the generator power is the necessary for the almost total compensation of the electric energy consumed by the turnery. The result obtained in the sizing of the photovoltaic system indicates that a power of 107.57 KWp is needed to suppress the need. This work also shows the documents and projects required for approval at the COPEL concessionaire, in addition to forecasting the cost of the installed photovoltaic system.